HOUSEHOLD FOOD WASTE POLICY: A LITERATURE REVIEW - Rian Diana; Drajat Martianto; Yayuk Farida Baliwati; Dadang Sukandar; Agung Hendriadi (Universitas Airlangga, 2022)
Introduction: Food waste (FW) is a serious problem and significantly impacts the environment, economy, and social. Globally, the average FW reaches 121 kg/ capita/year, and households are the main contributors to FW. Several countries have implemented various strategies to prevent household FW. This review aims to explore the household FW prevention policies and their potential to be implemented in Indonesia. Discussion: Three strategies have been widely applied worldwide, including economic incentives, regulations, as well as FW awareness and behavior campaigns. In this case, the economic incentives include landfill tax, incineration tax, and Pay-As-You-Throw (PAYT). Many laws and regulations have been implemented related to waste management, food, economics, and those regulations are either directly or indirectly related to FW. The awareness and behavior change campaign is the most widely applied strategy to prevent household FW globally. Conclusion: Well-designed policies and regulations supported by education and awareness campaigns are the potential strategies for household food waste reduction and prevention in Indonesia.